DETERMINATION OF ZMHKT1,5 GENE EXPRESSION UNDER DIFFERENT SALT STRESSES USING PLANT TISSUE CULTURE of MAIZE (ZEA MAYS L.). - & et al., Al-Salihy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was designed to determine ZmHKT1;5 gene expression in relatively salt tolerant using four maize genotypes (Alfajr and Almaha and medium-tolerant ones T1 and T6) within cellular level. Three salinity levels (2, 8, and 16 ds / m . Were used immature seeds were surface sterilized and embryos were dissected under full sterilization conditions. Callus was initiated from immature embryos of the above four genotypes on Skoog and Murashige (MS) medium supplemented with the required growth regulators (3 mg/L 2,4-D +0.5 mg/L kinetin) and recultured for three times and transferred to the stress medium containing NaCl. K+/Na+ and Ca+ / Na+ were measured and ZmHKT1;5 gene expression was estimated using Real-time PCR in callus cultures after tree cultures. Results indicated that a significant decrease in calcium and potassium ion concentrations with increasing NaCl level. The highest concentration was recorded in the genotype Almaha, while the lowest was in Alfajr. The highest concentration of gene ZmHKT1;5 expression was achieved in the Alfajr genotype reached 5.59 at 16 ds/m.